Cover Feature: Nanorods Based on Mesoporous Silica Containing Iron Oxide Nanoparticles as Catalytic Nanomotors: Study of Motion Dynamics (2/2021). Issue 2 (19th January 2021) - Mestre, Rafael; Cadefau, Núria; Hortelão, Ana C.; Grzelak, Jan; Gich, Martí; Roig, Anna; Sánchez, Samuel
Abstract : Mesoporous silica nanorods (MSNRs) are presented as interesting new chassis for the development of catalytic nanomotors due to their longitudinal pores, their rod‐like structure and versatile material. Three types of MSNR nanomotors, based on Pt catalysis, Fenton‐like reactions of embedded Fe2 O3 nanoparticles inside the mesopores, and their synergistic combination, are demonstrated to self‐propel upon addition of hydrogen peroxide. Two sub‐populations of motors moving by either enhanced diffusion or ballistic propulsion are shown to coexist in this system. More information can be found in the Full Paper by Samuel Sánchez, Anna Roig et al.